Nonlinear ion–acoustic waves in an inhomogeneous plasma with non-thermal distribution of electrons - Singh, S.V. (My University, 2015)
In the Earth's magnetosphere, the boundary layer regions are the sources for inhomogeneous plasmas and are natural laboratories to study wave phenomena. In these regions, particles distributions also differ from Maxwellian and are found to be non-thermal. Therefore, amplitude of the waves propagating through these regions can vary differently compared to the homogeneous plasmas. In this study, propagation of ion–acoustic waves (IAWs) in an inhomogeneous, warm electron-ion plasma is examined. The electrons are considered to be having non-thermal Cairn's type distribution and ions follow the fluid dynamical equations. Further, inhomogeneity is assumed in equilibrium density of the electrons and ions. The evolution of the nonlinear IAWs is governed by the Korteweg–de Vries (KdV) equation with variable coefficients. Analytical solution of the KdV equation shows that for a cold ion plasma and non-thermal electrons, the amplitude and the width of the nonlinear IAWs decreases and increases, respectively with the inclusion of the non-thermal distribution of electrons. It is interesting to note that nonlinear IAWs in this model can not propagate for whole range of non-thermal parameter, α. The novel result of this study is that for nonlinear IAWs to propagate in the inhomogeneous two component plasma with ions and non-thermal electrons, the non-thermal parameter, α ≤ 0.155. Results from our study may have impact on the propagation of the IAWs in the boundary layer regions of the Earth's magnetosphere where density inhomogeneities are appreciable.
Keywords: Nonlinear ion–acoustic waves; Earth's magnetosphere; Boundary layer; Korteweg–de Vries (KdV); IAW